Feasibility of mail-based biospecimen collection in an online preconception cohort study - Koenig, Martha R.; Wesselink, Amelia K.; Kuriyama, Andrea S.; Chaiyasarikul, Alina; Hatch, Elizabeth E.; Wise, Lauren A. (Frontiers in Reproductive Health, 2023)
Background: Prospective cohort studies that enroll participants before conception are crucial for deepening scientific understanding of how the preconception environment influences reproductive outcomes. While web-based research methods provide efficient and effective strategies to collect questionnaire-based data, few of these studies incorporate biospecimen collection, which can enhance the validity of exposure assessment. There is limited literature on the feasibility and cost-effectiveness of collecting biospecimens in web-based preconception cohort studies. Methods: We evaluated the feasibility and cost-effectiveness of in-clinic and mail-based biospecimen collection in Pregnancy Study Online (PRESTO), a North American web-based preconception cohort study. Both members of the couple were eligible to participate if their conception attempt time was ≤3 months at enrollment. We invited study participants from the Boston, MA and Detroit, MI metropolitan areas to attend a study visit and provide urine and blood (hereafter "in-clinic protocol"). We invited all other participants to complete mail-based collection of urine and blood spots (hereafter "mail-based protocol"). We compared overall consent and protocol completion rates, demographic characteristics of those who consented and completed either of the protocols, and costs between mail-based and in-clinic protocols for biospecimen collection. Finally, we described logistical challenges pertaining to reliance on mail-based delivery of time-sensitive biospecimens compared with in-clinic methods. Results: During January 2022-July 2022, 69% of female participants (134/195) and 42% of male participants (31/74) consented to participate in the mail-based protocol. Consent rates for the in-clinic protocol were 39% for female participants (289/739 during March 2014-July 2022) and 25% for male participants (40/157 during March 2017-July 2022). Participants who consented to participate were generally of higher socioeconomic position than non-participants. Deviations from the protocol occurred more frequently within the mail-based protocol but were easily corrected. The cost per participant enrolled was similar across protocols (mail-based: $276.14 vs. in-clinic: $270.38). Conclusions: Our results indicate that mail-based collection of biospecimens may create opportunities to recruit a larger and more geographically diverse participant population at a comparable cost-per-participant enrolled to in-clinic methods.